Bioversity International Annual Report 2017 - Bioversity International (Bioversity International, 2018)
The Annual Report contains highlights of Bioversity International research activities to deliver scientific evidence, management practices and policy options to use and safeguard agricultural and tree biodiversity to attain sustainable global food and nutrition security.